Insight and Behaviour of General Population Regarding Modifiable Risk Factors for the Prevention of Cardiovascular Disease - Saima Naz Mohsin, Ambreen Muddassir, Abdul Shakoor, Amir Razi, Isba Muzaffar Khan, Shazia Ateeq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the awareness of general population regarding risk factors and prevention of cardiovascular disease (CVD). Study Design: Cross-sectional study Place and Duration of Study: Department of Medicine, Shaikh Zayed Hospital Lahore from 1st January 2021 to 30th September 2021. Methodology: Four hundred and ninety two subjects were enrolled. A self-designed questionnaire was used to collect data concerning knowledge attitude and practices of study participants regarding CVD. Results: Majority of the participants were aware of the fact that by reducing BMI <25237(48.1%), good control of blood pressure335 (68.1%), regular exercise, 286(58.1%), reduce stress 457(92.9%), and avoid smoking 391(79.5%) were the majors modification of risk factors that are required for the prevention of CVD. Only few 76(15.4%), 120(24.4%) 54(10.9%) were aware of other risk factors modification including; maintain high level of HDL and maintain low levels of LDL, avoidance smokeless tobacco respectively as preventive measure of CVD. However there was a misconception that the fatty meals and saturated fats do not increase cholesterol and are beneficial for heart health. Major reasons for not being able to adopt a healthy lifestyle were limited access to outdoor and indoor exercise (68%), financial constraints (61%) inability of individuals to avoid passive smoking (51%) and busy life style (44%). Conclusion: General population has sufficient knowledge regarding risk factors and prevention of CVD. Somehow they are not practicing healthy lifestyle for disease prevention. There is a need to counsel people to adopt healthy lifestyle and avoid risk factors leading to CVD.